Movimentos socioambientais e gestão dos recursos naturais no cenário amazônico: Ações da Confederação dos Povos Indígenas na Bolívia / Social environmental movements and management natural resources in the Amazon scenario: Action of indigenous confederation in Bolivia. - Luciana Aparecida Iotti Ziglio; Maria Angela Comegna (Sociedade & Natureza)
Provide inputs for the analysis of training and performance of environmental movements and rethink the ways of managing natural resources and conflicts arising that are in progress are justifications for this study. The aim is thus to offer both elements that can contribute to studies of models of natural resource management, as support future policies to promote sustainable regional development. Thus, in light of the concepts of sustainable development and environmental rationality, we tried to verify the performance of the Confederation of Indigenous People of Bolivia - CIDOB face to environmental issues and their influence on social practices related to the conservation and sustainability of natural resources. Therefore, it was used as working methodology analysis of literature on the topic and documents produced by CIDOB, many of them accessed electronically.